Leadership attributes of Tan Sri Muhyiddin Yassin, The eighth Malaysian Prime Minister - Syed Arabi Idid,; Zeti Azreen Ahmad,; Imran, Ssemuddu (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study examines the leadership and personality traits of Tan Sri Muhyiddin Yassin, the 8th Prime Minister of Malaysia, based on an open-ended response provided by Malaysian voters. Studying leadership contributes to a greater understanding of the leaders’ role in society as they supposedly inspire others towards attaining citizenship goals. Still, if wrongly led, they would also damage the country. Leadership has gained importance as a field of study, although the focus is still Western-centric. There are studies on good and bad leaders covering various sectors. Despite the outcome of the recent 15th general election, Malaysia is still regarded as one of Asia’s most politically stable countries, having had one-party leadership since independence. Studies on Malaysian leadership have been scarce. This study focuses on Tan Sri Muhyiddin Yassin, a seasoned politician whose strategy brought him to occupy the highest office in Malaysia. The exploratory research using a qualitative approach probed how Malaysians perceived his leadership and personality traits when he was the Prime Minister. A research design using a questionnaire was used in this study to collect data on 822 respondents from a nationwide survey. The findings showed that Malaysians identified certain traits of leadership and their prime minister’s personality. Still, there were differences in identifying them among the three racial groups in the country. The characteristics collected were then collapsed into categories to understand the Malaysian leader.